Growth Trends of Internet Users and E-commerce in Increasing Economic Growth in Indonesia - Maisaroh, Neng; Habibi, Ahmad; Iqbal, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2024)
Indonesia as the country with the largest population in Southeast Asia has great potential to increase internet penetration and utilize digital technology to increase economic growth and people's welfare. This study aims to analyze the growth trend of internet and e-commerce users in increasing economic growth in Indonesia. The research method used is qualitative descriptive by collecting secondary data from various sources, such as Report Data, scientific articles, and literature sources related to the research topic. The results of this study show that the growth of internet and e-commerce users in Indonesia has a positive impact on economic growth by increasing business opportunities, enabling easy and fast transactions, and encouraging the region's economy to be more even. The development of e-commerce can help MSMEs improve the quality of information and position a wider market. Government participation is very important to maximize the potential of e-commerce as the main driver of economic growth in Indonesia.